The rainbow business (does not) wants you: um estudo sobre políticas organizacionais de inclusão de trabalhadores LGBTs - Juliani, Rafael Paulino (Universidade Federal de São Carlos, 2022)
Notwithstanding the psychosocial exclusion practices of LGBT workers (lesbians, gays, bisexuals and transgenders) from the world of work, verified to the present day, there is a counter-hegemonic movement of inclusion, through few, but significant, actions from international organizations, public authorities and even by the private sector. Despite the prejudices and violations experienced at work by LGBT people, this is still represented by them as a tool and means to overcome some barriers and assert themselves as social subjects. Faced with the paradox of pain and delight of being "LGBTWorkers" and at the same time there is also a growing and even active search for workers who do not fit the heteronormative standards to compose the staff of large organizations, there is a need to better understand the existence (or not) of correspondences between the values of the management system, expressed by the business discourse, and the organizational practices of the referred companies. This research aimed to evaluate how, in fact, the inclusion policies for LGBT workers, practiced by an organization that, avowedly, positions itself as inclusive and diverse are implemented. I adopted a qualitative method and carried out a case study, through direct observations, semi-structured interviews and survey of official documents. The information obtained from the field was analyzed through triangulation and made it possible to verify that the company studied, in fact, did not have diversity policies concretely implemented. It carried out few and punctual awareness actions to minimize tensions between LGBT workers and other workers, however, without setting real inclusion goals, mainly, for transgender people. a Corporate Social Hypocrisy, in the form of Rainbow Washing.
The rainbow business (does not) wants you: a study on organizational inclusion policies for LGBT workers
Keywords: Diversidade e inclusão; Políticas organizacionais; Gestão da diversidade LGBT; Trabalho; Maquiagem arco-íris; Diversity and inclusion; Organizational policies; LGBT diversity management; Work; Rainbow washing; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL